(untitled) (Altre Modernità, 2017)
The paper considers the lexis of error and examines its use across time in relation to the writing and spelling of English, to grammar and pronunciation. Discussion focuses first on the earliest records of notions of correctness in English language usage, from Ælfric forwards to the emergence of standard English, from the sixteenth century’s growing worries about copiousness and purity of diction to eighteenth-century concerns to prescribe and rule the language. The historical overview is complemented by consideration of the data drawn together by the Glasgow Historical Thesaurus project, its evidence taken from the Oxford English Dictionary and the Dictionary of Old English Corpus. For earlier centuries, there are by far fewer relevant citations, often buried within words wide in reference. With the help of the Historical Thesaurus we drill down to view how views of language mistakes and errors have changed over the centuries of the recorded history of English.